Functional Validation of an E-Commerce Website Prototype for the Digitalization of an Animal Feed MSMEs - Destya Permata Choerul; Dimas Albar Ismail; Arida Murti Martikasari (SAINTEKS : Jurnal Sain dan Teknik, 2026)
The development of digital technology has encouraged MSMEs to start adopting online sales systems to improve the efficiency of transaction management. However, some MSMEs still carry out business processes manually without the support of an intergrated system. This study aims to design and test an e-commerce website prototype as an initial model for digitization in animal feed MSMEs. This study uses a software engineering approach with the Waterfall method System Development Life Cycle (SDLC) model, which includes the stages of requirements analysis, design, implementation, and testing. The system was developed using PHP and MySQL and run on a localhost environment. Testing was conducted using the Black Box Testing method to verify the suitability of the system functions with the requirements specifications. The results of the study show that all the main features, such as product management, shopping cart, checkout process, and transaction recording, work according to the design. This study produced a functionally feasible system design as the initial stage of e-commerce system implementation in animal feed MSMEs. Further testing in an online environment and user evaluation are needed to assess the effectiveness of the system empirically.   Keywords: e-commerce, MSMEs, digitalization, website